Isolated greater trochanter fractures - Aprato, Alessandro; Cipolla, Alessandra; D'Amelio, Andrea; Branca Vergano, Luigi; Giaretta, Stefano; Massè, Alessandro (Acta Biomedica Atenei Parmensis, 2023)
Introduction: Isolated fractures of the greater trochanter (GT) in adults are rare injuries and traditionally treated without surgery. The present systematic review was designed to examine the treatment protocol for isolated GT fractures and to discover if innovative surgical techniques, such as arthroscopy or suture anchors, can be used to improve outcomes in young active patients.Methods: A systematic review was conducted including all full-text articles suited our inclusion criteria from January 2000 describing treatment protocols of isolated great trochanter fractures confirmed at MRI in adults.Results: The searches identified a total of 247 patients from 20 studies with a mean age 56.1 years and mean follow-up 13,7 months. Only 4 case report treated 4 patients with not unique surgical strategy. The rest of the patients were treated conservatively.Discussion: Most trochanteric fractures can heal without surgical intervention with good results However, the patient must not immediately bear full weight and the abductor’s function could decrease. Displaced GT fragments more than 2 cm or athletes, young, demanding patients may benefit from surgical fixation to regain abductor function and strength. Evidence-based surgical strategies could be provided by arthroplasty and periprosthetic literature.Conclusion: The grade of fracture displacement and the physical demands of the athlete can be important factors in the decision process for or against surgery. By now, no evidence-based guideline exists for the ideal treatment method in demanding patients. It is necessary use a “patient-specific” treatment strategy.